Evaluation the Antibacterial Activity of the Brine, Nisin Solution, and Ozonated Water Against E. coli O157:H7 in the Experimentally Local Produced Soft Cheese - Khudhir, Zina S (The Iraqi Journal of Veterinary Medicine, 2021)
This study aimed to evaluate the antibacterial efficacy of brine solution in compared to nisin and ozonated water treatments against E. coli O157:H7 in experimentally local produced soft cheese (ELPSC). A total of 25 raw cow milk samples were collected from farmers and local markets in Baghdad city and utilized to manufacturing 25 of ELPSC samples following the traditional procedure in rural Iraq without salting or heat treatment. Bacteriological analysis for potential E. coli O157:H7 contamination was performed and confirmed by cultural, biochemical, and serological tests. Antibacterial activity of brine solution (7% w/v), nisin solution (100 IU/mL), and ozonated water (0.6 ppm) was performed for positive samples after 2 h contact time at ambient temperature. Positive isolates of E. coli O157:H7 were detected and confirmed as 3 out of 25 cheese samples (12%), with initial average bacterial count of 6.146 log10 CFU/g. The initial bacterial count was significantly (P<0.05) reduced to 3.778, 4.380 and 4.544 log10 CFU/g when subjected to brine salting, nisin solution, and ozonated water, respectively. Cheese samples exposed to brine had a significantly (P<0.05) higher reduction in the bacterial growth than those exposed to nisin or ozonated water treatments for each alone. More effective reduction in E. coli O157:H7 bacterial growth was not observed when brining exposure time elongated at ambient temperature to 6 h. These findings may be useful in raising the public knowledge about the use of brine solution as a domestic antibacterial approach for minimizing the possible risk of E. coli O157:H7 contamination in the local produced soft cheese.